Viral determinants of the variable sensitivity of herpes simplex virus strains to gD-mediated interference. - Dean, H J (1995)
Cells that express glycoprotein D (gD) of herpes simplex virus type 1 (HSV-1) resist infection by HSV-1 and HSV-2 because of interference with viral penetration. The results presented here show that both HSV-1 and HSV-2 gD can mediate interference and that various HSV-1 and HSV-2 strains differ in sensitivity to this interference. The relative degree of sensitivity was not necessarily dependent on whether the cell expressed the heterologous or homologous form of gD but rather on the properties of the virus. Marker transfer experiments revealed that the allele of gD expressed by the virus was a major determinant of sensitivity to interference. Amino acid substitutions in the most distal part of the gD ectodomain had a major effect, but substitutions solely in the cytoplasmic domain also influenced sensitivity to interference. In addition, evidence was obtained that another viral gene(s) in addition to the one encoding gD can influence sensitivity to interference. The results indicate that HSV-1 and HSV-2 gD share determinants required to mediate interference with infection by HSV of either serotype and that the pathway of HSV entry that is blocked by expression of cell-associated gD can be cleared or bypassed through subtle alterations in virion-associated proteins, particularly gD.